Two new subterranean species of Hyalella Smith, 1874 (Crustacea: Amphipoda: Hyalellidae) from Brazil - Cardoso, Giovanna Monticelli; Araujo, Paula Beatriz; de Pádua Bueno, Alessandra Angélica; Ferreira, Rodrigo Lopes (Zootaxa, 2014)
Two new species of Hyalella from Brazil are described. Hyalella veredae sp. n. shows the following characters: eyes reduced or absent in some specimens; antenna 1 and antenna 2 of similar size, and a curved seta on the inner ramus of male uropod 1. Hyalella formosa sp. n. is characterized by the absence of eyes, antenna 1 longer than antenna 2 and a curved seta on the inner ramus of male uropod 1. The species were found on caves located in two private properties, both under the impact of agricultural activities, which demonstrates a potential threat to these subterranean environments.